Національна історико-культурна спадщина: новітні засоби збереження та використання - Божук, Людмила; Клиніна, Тетяна (Видавництво Львівської політехніки, 2019)
The article describes modern information and communication technologies as means of preservation, access and use of historical and cultural heritage, the advantages, possibilities and prospects of interactive means of representation of the national cultural heritage are described.
Keywords: historical and cultural heritage; information and communication technologies; electronic resources; interactive means of representing the national cultural heritage